Hydrophobic MOFs for the efficient capture of highly polar volatile organic compound. Issue 8 (2nd February 2023) - Severino, Maria Inês; Al Mohtar, Abeer; Soares, Carla Vieira; Kolmykov, Oleksii; Freitas, Cátia; Dovgaliuk, Iurii; Martineau, Charlotte; Pimenta, Vanessa; Nouar, Farid; Maurin, Guillaume; Pinto, Moisés L.; Serre, Christian
Abstract : Effective capture of polar volatile organic compounds under environmental conditions is a challenge owing to the adsorption competition between polar volatile organic compounds and water. Abstract : Effective capture of polar volatile organic compounds under environmental conditions is a challenge owing to the adsorption competition between polar volatile organic compounds and water. The best adsorbents usually exhibit a compromise between a moderate affinity towards the VOC and hydrophobicity. Herein, by conducting experimental (sorption isotherms, dynamic measurements, X-ray diffraction, and solid-state NMR) and computational (Monte Carlo and density functional theory) studies, we demonstrate that introducing perfluorinated groups within the flexible microporous MOF increases hydrophobicity and its MIL-53(Al) MOF increases hydrophobilicty and leads to higher affinity to VOCs. Remarkably, MIL-53(Al)-CF3 exhibits an outstanding affinity for acetic acid even in the presence of water, while its MIL-53(Al)-2CF3 analogue, owing to steric hindrance, is not efficient. Therefore, perfluorinated flexible MIL-53(Al) with one CF3 group appears as an optimum sorbent for indoor air quality management under real working conditions, especially for high-end applications that require the removal of trace levels of VOCs under environmental conditions.